2012
DOI: 10.1103/physrevlett.108.224801
|View full text |Cite
|
Sign up to set email alerts
|

Multicavity X-Ray Fabry-Perot Resonance with Ultrahigh Resolution and Contrast

Abstract: Realization of x-ray Fabry-Perot (FP) resonance in back-Bragg-reflection crystal cavities has been proposed and explored for many years, but to date no satisfactory performance has been achieved. Here we show that single-cavity crystal resonators intrinsically have limited finesse and efficiency. To break this limit, we demonstrate that monolithic multicavity resonators with equal-width cavities and specific plate thickness ratios can generate ultrahigh-resolution FP resonance with high efficiency, steep peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 25 publications
4
65
0
Order By: Relevance
“…Skyrmion lattice (SkX) is classified as a typical topological excitation. The formation of SkX is reported in thin films of B20 transition metal compounds, Fe 0.5 Co 0.5 Si [2], FeGe [3,4] where as the precursor states as A-phase are observed in single crystalline Fe 0.8 Co 0.2 Si [5], MnSi [1,6,7] and FeGe [8,9]. Such observation is also reported in thin films as well as bulk form of multiferroic insulating compound Cu 2 OSeO 3 [10,11].…”
Section: Introductionmentioning
confidence: 72%
“…Skyrmion lattice (SkX) is classified as a typical topological excitation. The formation of SkX is reported in thin films of B20 transition metal compounds, Fe 0.5 Co 0.5 Si [2], FeGe [3,4] where as the precursor states as A-phase are observed in single crystalline Fe 0.8 Co 0.2 Si [5], MnSi [1,6,7] and FeGe [8,9]. Such observation is also reported in thin films as well as bulk form of multiferroic insulating compound Cu 2 OSeO 3 [10,11].…”
Section: Introductionmentioning
confidence: 72%
“…The physics of skyrmions and chiral modulations in the cubic helimagnets has gained great importance, in recent times. Generally, chiral modulations in non-centrosymmetric magnets (chiral, cones, and skyrmions) can be separated into two fundamentally different classes, (i) regular modulations with fixed magnetization amplitude and rotational modes arising in a wide temperature interval [1][2][3] and (ii) precursor modulations with a soften magnetization amplitude in the vicinity of longrange magnetic ordering, T c [4][5][6][7]. MnSi is a weak itinerant metal that orders helically below 30 K (T c ∼ 29.7 K) due to Dzyaloshinkskii-Moriya (DM) interactions as a result of the lack of inversion symmetry [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…THE has been observed in metallic magnets with chiral crystal structure and skyrmionic phases such as B20 compounds (e.g., MnSi) [2,3,6], pointing out that THE is a powerful tool for probing the skyrmion phase. Hall effect measurements of epitaxial FeGe grown on Si(111) substrates revealed a strong topological Hall effect after subtracting out the ordinary and anomalous Hall effects, demonstrating the formation of high density skyrmions between 5 and 275 K, in zero-magnetic field [7,8]. However, careful analyses of the Hall effect data measured on epitaxial films of MnSi/Si(111), corroborated with transmission electron microscopy observations of the magnetic domains, demonstrated that the additional contributions to the anomalous Hall resistivity, taken previously as a THE effect induced by skyrmions, are not due to the skyrmion magnetic phase but rather to the conical phase [9].…”
mentioning
confidence: 99%